Analisis Efektivitas Program Jaminan Kecelakaan Kerja Pada Badan Penyelenggara Jaminan Sosial Ketenagakerjaaan Kantor Cabang Cilandak Jakarta Selatan - Farrel Jabat Handimsah Putra; Abdul Rahman (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
Effectiveness is a fundamental component that functions to achieve the goals and objectives that have been set in an organization or program. BPJS organizes the Work Accident Insurance (JKK) program to provide protection and a sense of security to workers against the risk of work accidents in the form of financial support. This research was conducted using a qualitative approach, using data collection techniques in the form of interviews, field observations, and documentation reviews. The data analysis process includes the stages of data reduction, information presentation, and drawing conclusions. To ensure the validity of the data, this study uses a triangulation method that includes source triangulation, technique triangulation, and time triangulation. The findings of this study indicate that in general the implementation of the work accident insurance program at BPJS Ketenagakerjaan has been carried out effectively, in accordance with the three main indicators of effectiveness used as references in this study. However, in the indicator of achieving program objectives, there are still several targets that have not been fully realized. Therefore, it can be concluded that the Work Accident Insurance program at the BPJS Ketenagakerjaan Cilandak Branch Office, South Jakarta, has shown good effectiveness, although there is still room for improvement, especially in terms of achieving program objectives as a whole.